In the Belly of the Beast: A Comparison of the Evolution and Status of Prisoners' Rights in the United States and Europe - Harding, Roberta M. (1998)
Another epidemic has hit the international community. This one, however, is not derived from an unknown bacterial agent. Instead, it originates from a variety of social agents. The epidemic? The explosion in the number of people incarcerated in the global community. As of June 1997, the United States' prison population exceeded 1,700,000. This figure is consistent with the United States' status as one of the world's largest jailers. Like the United States, Europe's prison population has escalated. The growth in France's prison population is representative of the epidemic's trans-Atlantic scope. The Article is divided into several sections. The first section has subsections that explore and compare the historical development of prisoners' rights in the respective jurisdictions. Thus, each era of the evolution of the rights of the incarcerated in the United States will be identified, described, and discussed. The section devoted to the development of the rights of the incarcerated in Europe contains a brief survey of the status of prisoners' rights during the pre-World War II era. It then focuses on the evolution of these rights after World War II, the pivotal European era. This section also introduces and discusses several important regional public international law instruments that have a significant impact on the rights of imprisoned persons. The final section compares the progress taken by the United States and Europe and also examines the current differences and similarities in the status of the prisoners' rights in both jurisdictions